REFLEKSI PEMBELAJARAN: MODIFIKASI PROBLEM BASED LEARNING UNTUK MENDESKRIPSIKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA: Learning Reflection: Modification of Problem Based Learning to Descript Students Critical Thinking Ability (FPMIPA IKIP PGRI Bali, 2019)
It is undeniable, completing the final assignment is still a scourge for students. To minimize the improvement of the learning process, it should be done in stages and continuously. In addition, there needs to be an evaluation and reflection of learning to find out the obstacles and find alternative solutions for subsequent learning. The research subjects were VII semester students of the 2017/2018 academic year. This study uses the following instruments Learning Unit, Observation Sheet, Student Worksheet, Test Questions, and Field Notes. This article wants to present a description of the results of the reflection of learning that has been done on the subject of thesis writing techniques in the hope of providing a learning experience that can train students' critical thinking skills. The conclusions taken are through Problem Based Learning (PBL) that can be identified by students' critical thinking skills, the critical thinking indicators that are mostly owned by mathematics education students IKIP PGRI Jember namely Interpretation, the least critical indicator possessed by students is Recognition of assumptions.